Genetic and epigenetic aspects of depression and somatic disorders comorbidityon and somatic disorders comorbidity - G. V. Rukavishnikov; G. E. Mazo; N. G. Neznanov; A. O. Kibitov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
Complicated cascade of shared biological components with a genetic basis and, probably, common triggers of the genetically posed risk are involved in the comorbidity of depressive symptoms and somatic disorders. This suggests that, under certain conditions, it can manifest both a single disease and a cluster of disorders with different phenomenological characteristics, united by common genetically mediated pathophysiological mechanisms. Based on the analysis of epidemiological, clinical, pathophysiological and genetic studies, we substantiated the hypothesis of cluster genetic comorbidity of depression and somatic diseases.